FAKTOR FINANSIAL DAN NILAI PERUSAHAAN RITEL INDONESIA - Alexander, Ferdinand Morin; Sasmitapura, Angga; Michael, Michael; Meythi, Meythi (Widya Mandala Surabaya Catholic University, 2023)
Research Purposes. The aim of this study is to delve into several factors that can fortify the firm value of retail companies during a crisis period, such as operational efficiency, financing ability, and investment returns.Research Methods. The research employs a panel regression analysis technique on retail companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2021.Research Results and Findings. The study's findings reveal that operational efficiency and financing ability can affect firm value during a crisis, whereas investment returns do not. The results of this study can assist retail companies in formulating business strategies and provide insights for investors during the decision-making process for investments in the retail sector amid a crisis.